HOUSEHOLD RISK FACTORS FOR LASSA FEVER TRANSMISSION IN HIGH- AND LOW-BURDEN STATES OF NIGERIA: A COMPARATIVE CROSS-SECTIONAL SURVEY - Olanrewaju Olaiya; Kayode Akanbi; Kwarbai Aaron Maitala; Adamu Ishaku Akyala; Islamiyat Adekemi Olatinwo; Abah Michael Idoko; Imaobong Udo Isang; Olasunkanmi Samson Coker (INTERNATIONAL JOURNAL OF PUBLIC HEALTH RESEARCH AND DEVELOPMENT, 2026)
Lassa fever is a viral haemorrhagic fever endemic to Nigeria that exacts a heavy toll of morbidity and mortality annually. While Nigeria experiences annual outbreaks of the disease, household-level risk factors for transmission in areas of both high and low disease burden have not been fully described. The objective of this study was to evaluate and compare household risk factors for Lassa fever transmission in two high-burden (Ondo and Edo) and two low-burden (Bauchi and Ebonyi) states in Nigeria. Four states (sample size determined by quota sampling) were purposively selected and each allocated 150 consenting adult respondents yielding an overall sample size of 600 respondents. Multistage stratified random sampling technique was employed. Data on fourteen variables were collected using a pre-tested structured questionnaire. The variables include; household history of LF; frequency of rodents per sighting; food storing habits; prevention practices against rodents; awareness about LF; accessibility to healthcare facilities; respondents who had ever attended health training; ever diagnosed with LF in the last five years; severity of symptoms; disease outcome; age distribution; respondents’ educational status; household hygiene level and hand washing practices among others. Responses for each independent variable were analysed using descriptive statistics and the results were presented based on states with high LF burden versus states with low LF burden. Among the respondents, 35.3% reported previous history of Lassa fever case in the household and 32.7% were not sure if they had a prior history of Lassa fever case. 42.0 percent of respondents reported seeing rodents daily or weekly in and around their households. Only 35.0% of households stored food in sealed containers. 36.7 percent practiced rodent preventive measures. 68.7 % reported that they had heard of Lassa fever prior to survey completion. Overall, there seemed to be gap between awareness of LF and taking preventative measures. 53.3 percent of participants reported challenges accessing health care. 53.3 percent of respondents reported that they had never participated in any health training about Lassa fever. 33.3% of the respondents have been diagnosed with Lassa fever in the past five years. Ten percent of respondents have had someone in their home die from Lassa fever. 46.7 % of respondents self-reported their hygiene practices as being either fair or poor. 30.0 percent of respondents stated that they always washed their hands. Those who responded from high burden states reported higher frequencies of rodent sightings, less frequent use of sealed storage containers, and more challenges with healthcare access when compared to respondents from low burden states. Persistent rodent exposure, unsafe food storage, low adoption of preventive measures, healthcare inaccessibility, and suboptimal hygiene are widespread across all four states and are more pronounced in high-burden states. A significant awareness-to-action gap indicates that knowledge alone is insufficient to change behaviour. Integrated community-level interventions addressing rodent control, food storage, health education outreach, and primary healthcare strengthening are urgently required and should be embedded within a One Health framework.